EVALUATION OF WASTE FACILITY NEEDS BASED ON THE EXISTING POSITION AND THE AMOUNT OF WASTE VOLUME IN JEMPONG BARU-MATARAM VILLAGE - Wijana, Made; Suartika, I Made; Joniarta, I Wayan (Energy, Materials and Product Design, 2022)
An increase in the volume of waste if it is not accompanied by good management, will certainly have a bad impact on reducing the quality of the environment. In Jempong Baru village which has a population of 17,172 people, but currently only has 1 TPS located in the east Jempong neighborhood which has an area of 36 m3 with a capacity of 72 m3 and 1 damtruck with a capacity of 7 m3, which should be insufficient facilities, but in fact there is no garbage overflowing out of the TPS. For this reason, it is necessary to further study the current real condition (existing position) compared to the condition if all villages dispose of waste at the TPS in the environment of the research site (alternative position), in terms of the size of the volume of waste and the number of minimal waste facilities needed. The result of this study is that a dumptruck with a capacity of 7 m3 is able to transport waste from the TPS to the landfill, which is as much as 3 times / day (3 irritations). The total amount of waste generated in Jempong Baru Village in the existing position is 28.97 m3 / day and in the alternative position of 121.47 m3 / day. In the existing position, 1 TPS with a capacity of 72 m3 and 1 dumptruck with a capacity of 21m3 / day are sufficient. Meanwhile, in the alternative position, the facilities needed to handle the volume of waste as much as 121.47 m3 / day are at least 1 TPS and 6 dumptrucks